Estudo de primeiros princípios das propriedades eletrônicas de novos materiais derivados do grafeno : as nanofitas e nanofios - Oeiras, Rodrigo Yoshikawa (2012)
In this thesis, we study new materials derived from graphene, like nanowires and nanoribbons, with numerical calculations based on the density functional theory (DFT) and the non-equilibrium Green functions (NEGF). We will discuss these theories in general and we remark that these theories are based on quantum mechanical. The results of this study indicate that the carbon ribbons and carbon wires present interesting and not predictable structural properties. The analysis of the density of stated (DOS) and its variants (LDOs, PDOS, and COOP), provides the basis for understanding the structural properties and the electronic structure of the wires and ribbons. Whenever possible, we compare the results obtained with DFT and NEGF with simpler theories, such as the valence orbital theory and the molecular orbital theory. The results show that the transport current is robust and presents an anisotropy in transmission of electrons, indicating these materials are candidates for fabrication of electronic devices, such as transistors.